Crowdsourcing and Crowdfunding Platform using Blockchain and Collective Intelligence - Dhokley, Er.Waheeda; Gupta, Saurabh; Pawar, Ganesh; Shaikh, Abrar (International Journal of Computer Sciences and Engineering, 2019)
Startup companies are newly born companies or entrepreneurial ventures which are predominantly based on brilliant idea, innovation and statistical study. One of the preeminent obstacle of Startup’s is to seek capital and Human Intelligence to solve complex tasks of the product and in return bolster their project growth which can be achieved by ‘Crowdfunding’ and ‘Crowdsourcing’. Crowdfunding is a platform offering entrepreneurs and project owners the possibility to raise money from an undefined group of online users ie ‘Crowd’ while Crowdsourcing involves obtaining work,human intelligence or opinions from a large group of people which submit their data via the Internet. In this paper, we conceptualize a blockchain-based system “CrowdSF” for crowdsourcing and crowdfunding. In which we will try to integrate both platform together where idea creator can recruit the worker to execute the project or seek masses for funding their project at one single platform with security.